Influence Use Digital Payment Qris, And Financial Literacy on Gen Z's Consumptive Behavior - Santa Oktaviana Sinaga; Tiorika Nababan; Ananda Anugrah Nasution (Journal of Innovative and Creativity, 2026)
This study aims to analyze the influence of Digital Payment QRIS and Financial Literacy on the Consumptive Behavior of Generation Z at the Faculty of Psychology, Prima Indonesia University. The research employs an associative quantitative approach, collecting data through a Likert scale questionnaire distributed to 90 respondents selected using purposive sampling. The data were analyzed using multiple linear regression with SPSS. The findings indicate that Digital Payment QRIS has a positive and significant effect on consumer behavior, suggesting that the convenience and speed of digital transactions tend to increase impulsive buying among students. Conversely, Financial Literacy has a negative and significant effect on consumptive behavior, meaning that the higher the students' financial understanding, the lower their tendency to engage in consumptive behavior. Simultaneously, both variables contribute 94.5% to the consumptive behavior of Generation Z. These results highlights the importance of practical financial educational and mindful use of digital financial services to help students manage their spending more responsibly.